El “Canto a la Argentina”, de Rubén Darío, en la tradición métrica de la poesía hímnica - Utrera Torremocha, María Victoria (Rhythmica. Revista Española de Métrica Comparada, 2018)
En este trabajo se lleva a cabo un análisis métrico del “Canto a la Argentina” de Rubén Darío” en relación con la oda y el himno heroicos y con las nuevas vías rítmicas de la poesía moderna. En el poema de Darío se combinan diversos metros, entre los cuales los ritmos ternarios del eneasílabo y, especialmente, el decasílabo anapéstico en serie revelan la relación dialógica con la tradición épica y el “Himno Nacional” argentino. In this study, a metrical analysis is undertaken of Rubén Darío’s “Canto a la Argentina,” using the heroic ode and hymn as points of reference, together with the innovative rhythmic tendencies of modern poetry. In Darío’s poem, a range of metrical line types tend to interact, amongst which are to be found the triple-time type identifi able with the ‘toddaid’ quatrain tradition and, above all, the runs of anapaestic decasyllables which reveal a dialogic interaction with the epic tradition and the Argentine national anthem.